The EGPs: the eclosion hormone and cyclic GMP-regulated phosphoproteins. I. Appearance and partial characterization in the CNS of Manduca sexta - Morton, DB (J Neurosci, 1988)
The present study describes 2 phosphoproteins, both with an apparent molecular weight of 54 kDa, in the CNS of the tobacco hornworm, Manduca sexta. Their phosphorylation is regulated by a neuropeptide, eclosion hormone (EH), and the second messenger cGMP, which thus have been named the EGPs (eclosion hormone- and cGMP-regulated phosphoproteins). Although cAMP was more effective than cGMP at stimulating the phosphorylation of the EGPs in CNS homogenates, in the intact CNS cGMP was more effective. Since cGMP mediates the action of EH, this strongly suggests that cGMP is the second messenger that stimulates the phosphorylation of the EGPs in vivo. The EGPs can only be phosphorylated in vitro during discrete time periods during the life of Manduca. During the larval and pupal molts, the EGPs can first be phosphorylated just prior to ecdysis. Their ability to be phosphorylated is correlated with the time when the insect is sensitive to EH. This close temporal correlation suggests that the ability to phosphorylate the EGPs determines when the insect can first respond to EH. During adult development, the EGPs first appeared on fluorograms 6 d before sensitivity to EH, suggesting that at this stage other factors may also be involved in the regulation of sensitivity. For the ecdyses of all 3 stages, EH appeared to stimulate the phosphorylation of the EGPs at ecdysis. The EGPs were found in all regions of the prepupal nervous system that were investigated, but only in the abdominal and pterothoracic ganglia of the developing adult. Fractionation of nervous system homogenates by ultracentrifugation revealed that one of the EGPs was present only in the pellet fraction, whereas the other was approximately equally distributed between pellet and supernatant. Furthermore, the EGPs in the pellet fraction could be partially solubilized with detergents and high salt concentrations.